Optical Fiber Communication Conference 2017
DOI: 10.1364/ofc.2017.th2a.53
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Transmission Performance in Delay-Managed Few-Mode Fiber Links with Intermediate Coupling

Abstract: Linear equalization performance for delay-managed few-mode links in the nonlinear regime with intermediate linear coupling is studied for the first time. Existing fibers can allow similar performance per mode to that of uncoupled single-mode propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…For FMFs, we extend such an approach by assuming that the mode coupling also acts independently. Such approximations require h to be much shorter than the dispersion length T0 2 /|βu (2) | and the walk-off length T0/|βu (1) -βv (1) | where T0 is the pulse width, and shorter than the correlation length Lc defined 3 for XT(Lc) = [e 2 -1]/[e 2 + 1]. Fig.…”
Section: Nonlinear Fmf Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…For FMFs, we extend such an approach by assuming that the mode coupling also acts independently. Such approximations require h to be much shorter than the dispersion length T0 2 /|βu (2) | and the walk-off length T0/|βu (1) -βv (1) | where T0 is the pulse width, and shorter than the correlation length Lc defined 3 for XT(Lc) = [e 2 -1]/[e 2 + 1]. Fig.…”
Section: Nonlinear Fmf Modelmentioning
confidence: 99%
“…The linear mode coupling is modelled considering fibre sections with a random displacement of the core centre position 4 . The coupling is set by varying the amplitude of the variation in lateral section offset as explained in 3 .…”
Section: Nonlinear Fmf Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the nonlinear regime, it has been shown that MDM systems performance can be dominated by inter-mode interactions for low DMD and low XT [15], and that high XT significantly reduces intermodal nonlinear [16]. However, in the intermediate coupling regime, the nature of the dependence of the nonlinear distortion on the (distributed) XT strength and DMD has only recently started being studied [10,17] for mode delay uncompensated and compensated links. A significant number of works assume systems operating in the strong mode coupling regime, e.g.…”
Section: Introductionmentioning
confidence: 99%